EMPAGLIFLOZIN: TERAPI BARU UNTUK PASIEN GAGAL JANTUNG DENGAN KOMORBID DIABETES MELLITUS TIPE 2 (DMT2) - Maha Fitra ND (CV. ADIBA AISHA AMIRA, 2024)
Type 2 diabetes mellitus (DMT2) and heart failure have a strong relationship and one clinical outcome affects the other. Recent studies have succeeded in proving the benefits of empagliflozin, an SGLT2 inhibitor class drug (second-line drug for T2DM), on the cardiovascular system. In addition to the diuretic role, the cellular mechanism of empagliflozin that is known to play a role in animals is myocardial anti-fibrosis effect.